Impact of Maternal Death on Household Economy in Rural China: A Prospective Path Analysis - Ye, Fang (PLoS One, 2015)
OBJECTIVES: The present study aimed to explore the inter-relationships among maternal death, household economic status after the event, and potential influencing factors. METHODS: We conducted a prospective cohort study of households that had experienced maternal death (n = 195) and those that experienced childbirth without maternal death (n = 384) in rural China. All the households were interviewed after the event occurred and were followed up 12 months later. Structural equation modeling was used to test the relationship model, utilizing income and expenditure per capita in the following year after the event as the main outcome variables, maternal death as the predictor, and direct costs, the amount of money offset by positive and negative coping strategies, whether the husband remarried, and whether the newborn was alive as the mediators. RESULTS: In the following year after the event, the path analysis revealed a direct effect from maternal death to lower income per capita (standardized coefficient = -0.43, p = 0.041) and to lower expenditure per capita (standardized coefficient = -0.51, p<0.001). A significant indirect effect was found from maternal death to lower income and expenditure per capita mediated by the influencing factors of higher direct costs, less money from positive coping methods, more money from negative coping, and the survival of the newborn. CONCLUSION: This study analyzed the direct and indirect effects of maternal death on a household economy. The results provided evidence for better understanding the mechanism of how this event affects a household economy and provided a reference for social welfare policies to target the most vulnerable households that have suffered from maternal deaths.